Who wins the most when everybody wins? Predicting candidate performance in an authoritarian election. Issue 7 (3rd October 2019) - Fonseca Galvis, Ángela; Superti, Chiara
ABSTRACT: What explains the variation in vote shares received by candidates in single-party authoritarian elections where everybody wins? The scholarly literature has often ignored institutional variations, treated all authoritarian elections as similar, and explained the variation of vote shares as a consequence of clientelism, coercion or electoral fraud. We employ a unique data set for Cuba's 2013 National Assembly election to show an alternative answer: even in authoritarian regimes, institutional settings shape voters' behaviour and candidates' strategies. When the number of candidates on the ballot equals the number of parliamentary seats and yet voters can express some preference among multiple candidates, valence can become a predictor of candidate performance. Voters reward high-quality politicians, but not incumbents or Communist Party members, while candidates have no incentives to actively distinguish themselves and converge toward the general support of the single united slate.